Michael Henchard’s Frustration in Thomas Hardy’s the Mayor of Casterbridge - Abu Fanani; Achmad Zaidun; Amiq Amiq (Journal of English Education, Literature and Linguistics, 2022)
This study is about Michael Henchard’s frustration with Thomas Hardy the Mayor of Casterbridge. Using a qualitative approach and the theory of regression, the researcher finds that the main character behaves and speaks similarly to his character in his earlier years of life when he began a carrier. Thus, he undergoes a frustration that he behaves like before twenty years ago: abandoning others and escaping to liquor.